2018
DOI: 10.1007/s00705-018-3989-1
|View full text |Cite
|
Sign up to set email alerts
|

Croton golden mosaic virus: a new bipartite begomovirus isolated from Croton hirtus in Colombia

Abstract: A new begomovirus infecting Croton hirtus (Euphorbiaceae) from Colombia has been characterized. The complete DNA-A and DNA-B components were determined to be 2613 and 2551 nt in length, respectively, showing the typical genome organization of bipartite New World begomoviruses. DNA-A showed the highest nucleotide sequence identity (81.2%) to sida yellow mottle virus (JN411687), a begomovirus isolated from Sida rhombifolia in Cuba. Based on the current ICTV species demarcation criterion for the genus Begomovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Further studies are required to explore the infectivity, geographical distribution and host range of new begomoviruses. Recently, our research group reported the complete genome sequence of begomoviruses isolated from C. hirtus and R. minima, confirming them as new begomoviruses (Vaca-Vaca et al, 2018;López-López et al, 2019).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Further studies are required to explore the infectivity, geographical distribution and host range of new begomoviruses. Recently, our research group reported the complete genome sequence of begomoviruses isolated from C. hirtus and R. minima, confirming them as new begomoviruses (Vaca-Vaca et al, 2018;López-López et al, 2019).…”
Section: Resultsmentioning
confidence: 68%
“…In 2018 and 2019, the complete genomes of begomoviruses were found in C. hirtus and R. minima, both new begomoviruses with the proposed names Croton golden mosaic virus (CroGMV) and Rhynchosia golden mosaic Colombia virus (RhGMCV), respectively. (Vaca-Vaca et al, 2018;López-López et al, 2019). Recently, new begomovirus hosts were identified in a study conducted in Valle del Cauca on weeds associated with chili pepper crops: Parthenium hysterophorus, Malvastrum sp., Sida acuta, Acalypha sp., Euphorbia hirta, R. minima and R. humilis (Vaca-Vaca et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several species of begomoviruses have been reported in non-cultivated plants in the family Euphorbiaceae [7,8,9,10,11,12,13]. In Cnidoscolus urens, a wild host largely found in northeastern Brazil, only two viruses were reported: Cnidoscolus mosaic leaf deformation virus (CnMLDV) [14] and Cnidoscolus blistering yellow mosaic virus (CnBYMV) [not published].…”
Section: Main Textmentioning
confidence: 99%
“…y R. minima (Leguminosae) (Vaca-Vaca et al, 2011;López-López et al, 2012;López-López et al, 2014). Sin embargo, a la fecha sólo ha sido reportado la obtención del genoma completo de un begomovirus aislado de C. hirtus, el cuál fue denominado virus del mosaico dorado de Croton (croton golden mosaic virus, CroGMV) (Vaca-Vaca et al, 2018). Con base en lo anterior se hace necesario establecer las identidades moleculares plenas de otros begomovirus previamente detectados en las otras arvenses.…”
Section: Introductionunclassified